Geographical limits of the Southeastern distribution of Aedes aegypti (Diptera, Culicidae) in Argentina - Díaz Nieto, Leonardo M. (2013)
Aedes aegypti (Linnaeus) is a human-biting mosquito and the primary vector of human dengue and yellow fever viruses; it is also considered the principal vector of Chikungunya virus in Asia. In particular, dengue and dengue hemorrhagic fever constitute an important burden to humankind in terms of morbidity and mortality. About 3.6 billion people in the tropics, mainly in Asia, the Western Pacific region, the Caribbean, and Central and South America, live under risk of infection with one or more of the four dengue virus serotypes (DEN-1 to DEN-4), and recent reports estimate over 230 million infections, over 2 million cases of the severe form of the disease, and 21,000 deaths. (Párrafo extraído del texto a modo de resumen)